CO-JOINT BASED EVALUATION OF BEAN-BASED PROCESSED PRODUCTS AND THEIR ATTRIBUTES WITH CONSUMERS DATA IN MALAWI - Magreta, Ruth; Kaseka Regina; Katungi, Enid Mbabazi; Smith Nkata; Munthali, Justice; Fungo, Robert (2025)
The data served to evaluate consumer preferences for three processed bean products: bean flour, dehydrated pre-cooked beans, and bean paste. The study addressed several objectives, including identifying preferred product attributes, determining which were most valued, and comparing perceptions of processed versus unprocessed legumes. A key focus was assessing the acceptability of the prototypes after tasting and analyzing how acceptance correlated with consumer demographics and attitudes. The collected data encompassed participant characteristics, purchasing habits, attitudes, and their detailed feedback on the products after direct experience. Methodology:The research utilized a conjoint analysis framework to ascertain the relative importance of various bean product attributes. Data were collected from 120 participants using three LUANAR-developed prototypes and two structured instruments. Participants evaluated 12 attributes—comprising both intrinsic (e.g., taste, aroma, cooking time) and extrinsic (e.g., price, shelf life, packaging) factors—by providing a rating on a 5-point Likert scale and a ranked list of their top four preferences. To contextualize the quantitative findings, focus group discussions were conducted to gather community-level insights on bean consumption patterns and awareness. A separate checklist standardized the procedure for introducing the prototypes and collecting general feedback.